Constitutionalization of civil law through the jurisprudence of the peruvian Constitutional Court - Miranda Canales, Manuel Jesús (2016)
This article evidences the way of the Constitutional Law transcends the entire legal system and subjects to its provisions, constitutionalization which is strongly accentuated by the law of the Constitutional Court that complements and strengthens the legal institutions of Civil Law, in particular the Family Law.